Altered Growth, Pigmentation, and Antimicrobial Susceptibility Properties of Staphylococcus aureus Due to Loss of the Major Cold Shock Gene cspB - Duval, Brea D. (American Society for Microbiology (ASM), 2010)
An insertional mutation made in the major cold shock gene cspB in Staphylococcus aureus strain COL, a methicillin-resistant clinical isolate, yielded a mutant that displayed a reduced capacity to respond to cold shock and many phenotypic characteristics of S. aureus small-colony variants: a growth defect at 37°C, a reduction in pigmentation, and altered levels of susceptibility to many antimicrobials. In particular, a cspB null mutant displayed increased resistance to aminoglycosides, trimethoprim-sulfamethoxazole, and paraquat and increased susceptibility to daptomycin, teicoplanin, and methicillin. With the exception of the increased susceptibility to methicillin, which was due to a complete loss of the type I staphylococcal cassette chromosome mec element, these properties were restored to wild-type levels by complementation when cspB was expressed in trans. Taken together, our results link a stress response protein (CspB) of S. aureus to important phenotypic properties that include resistance to certain antimicrobials.